Soluble P-selectin and CD40L levels in subjects with prediabetes, diabetes mellitus, and metabolic syndrome—the Chennai Urban Rural Epidemiology Study - Gokulakrishnan, Kuppan; Deepa, Raj; Mohan, Viswanathan; Gross, Myron D. (Metabolism, clinical and experimental, 2006)
The aim of the study was to determine whether the levels of soluble P-selectin (sP-selectin) and soluble CD40L (sCD40L) are elevated in Asian Indian subjects with impaired glucose tolerance (IGT), diabetes, and metabolic syndrome (MS). Study subjects were recruited from the Chennai Urban Rural Epidemiology Study (CURES), an ongoing population-based study on a representative population of Chennai city in southern India, and were grouped as follows: group 1, normal glucose tolerance (NGT) (n = 60); group 2, IGT (n = 60); and group 3, type 2 diabetes mellitus (n = 60). Normal glucose tolerance, IGT, and diabetes were defined using World Health Organization consulting group criteria. The inclusion criteria were nonsmokers; normal resting 12-lead electrocardiogram; absence of angina, myocardial infarction, or history of any known vascular, infectious, or inflammatory diseases; and subjects not on statins or aspirin. Insulin resistance was calculated using the homeostasis assessment model using the formula: fasting insulin ( μIU/mL) × fasting glucose (mmol/L)/22.5. Soluble P-selectin and sCD40L were estimated by enzyme-linked immunosorbent assay. Metabolic syndrome was defined using Adult Treatment Panel III guidelines. Subjects with diabetes and IGT were older (diabetes: 53 ± 9 years, P < .01; IGT: 51 ± 10 years, P < .05) compared with the NGT group (48 ± 10 years). Subjects with diabetes and IGT had higher levels of sP-selectin (diabetes: 162 ± 79 ng/mL, P < .001; IGT: 102 ± 37 ng/mL, P < .001) compared with the NGT group (55 ± 48 ng/mL). Soluble CD40L levels were also higher in those with diabetes and IGT (diabetes: 3.2 ± 2.0 ng/mL, P < .001; IGT: 2.0 ± 1.3 ng/mL, P < .001) compared with the NGT group (1.1 ± 0.9 ng/mL). Subjects with MS had significantly higher levels of sP-selectin (with MS, 118 ± 76 ng/mL; without MS, 95 ± 66 ng/mL; P = .028) and sCD40L (with MS, 2.4 ± 1.8 ng/mL; without MS, 1.9 ± 1.5 ng/mL; P = .036) compared with subjects without MS. Among subjects with NGT and IGT, the mean levels of sP-selectin (tertile I, 65.0 ng/mL; tertile II, 80.0 ng/mL; tertile III, 91.0 ng/mL) and sCD40L levels (tertile I, 1.2 ng/mL; tertile II, 1.7 ng/mL; tertile III, 1.8 ng/mL) increased with increase in tertiles of homeostasis assessment model–insulin resistance, and the difference reached statistical significance in the last tertile compared with the first tertile ( P < .05). This study demonstrates that increased levels of sP-selectin and sCD40L are seen in Asian Indian subjects with IGT, type 2 diabetes mellitus, MS, and insulin resistance.